Barriers and facilitators to the adoption of physical activity policies in elementary schools from the perspective of principals: An application of the consolidated framework for implementation research–A cross-sectional study - Wendt, Janine; Scheller, Daniel A.; Flechtner-Mors, Marion; Meshkovska, Biljana; Luszczynska, Aleksandra; Lien, Nanna; Forberger, Sarah; Banik, Anna; Lobczowska, Karolina; Steinacker, Jürgen M. (Frontiers in Public Health, 2023)
Background Studies have shown that policies to promote physical activity in schools can have a positive impact on children's physical activity behavior. However, a large research gap exists as to what determinants may influence the adoption of such policies. Applying the Consolidated Framework for Implementation Research (CFIR), we investigated barriers and facilitators to the adoption of physical activity policies in elementary schools in Baden-Wuerttemberg, Germany, from the perspective of school principals. Methods A cross-sectional study was conducted between May and June 2021. School principals from elementary and special needs schools (n = 2,838) were invited to participate in the study. The online questionnaire used was developed based on the CFIR and included questions on school characteristics and constructs of the CFIR domains inner setting, characteristics of individuals, and process. Logistic regression analyses were performed to examine associations between policy adoption and school characteristics as well as CFIR determinants. Results In total, 121 schools (4%) participated in the survey, of which 49 (40.5%) reported having adopted a policy to promote physical activity. Positive associations with policy adoption were found for general willingness among teaching staff [odds ratio (OR): 5.37, 95% confidence interval (CI): 1.92–15.05], available resources (OR: 2.15, 95% CI: 1.18–3.91), access to knowledge and information (OR: 2.11, 95% CI: 1.09–4.09), and stakeholder engagement (OR: 3.47, 95% CI: 1.24–9.75). Conclusions This study provides a first insight into potential barriers and facilitators at the organizational level of schools that may be relevant to the adoption of physical activity policies, from the perspective of school principals. However, due to a low response rate, the results must be interpreted with caution. A strength of this study includes theoretical foundation through the use of the CFIR. The CFIR could be well-adapted to the school setting and provided valuable support for developing the questionnaire and interpreting the study results.